Conceptions of good psychological health and personality functioning of Filipino College students a multi-method investigation - Church, A. Timothy; Katigbak, Marcia S.; Castaneda, Imelda (Philippine Journal of Psychology, 1984)
Filipino college students' conceptions of good psychological health and personality functioning were studied using the critical incident technique, free-response listing of characteristics, in-depth interviews, and direct ratings on a combined sample for over 700 students in five Metro Manila universities. Content analysis of the healthy and unhealthy personality descriptors obtained delineated 54 categories or dimensions of healthy Filipino personality. These are related to the previous literature on Filipino personality and values and convergences and divergences noted. Some, but not all, sex differences in healthy conceptions replicated across methods. Females emphasized "psychic integration" and "social relations" concepts more, males "alert and logical thinking." Several within and across-method indices of perceived relative importance of the healthy concepts were compared. while considerable agreement was found between different free-response (frequency of mention) indices, free-response versus direct rating methods showed little agreement. In one difference, the free-response data was generally more "other" or "interpersonally" oriented. These multi-method finding suggest that the results of some previous Philippine studies on values or ideal personality traits may have been substantially determined by the method(s) used - usually free-response.